Analisis Faktor Penyebab Stock Out Obat di Gudang Farmasi RSI Ibnu Sina Padang - Dessy Angraini; Alfa Novitri; Budi Irawan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Stocking out drugs in hospital pharmacy warehouses is a serious problem and direct impact on the quality of health services. Running out of stock of medications can lead to delays in treatment and unavailability of needed therapies. Based on the initial interview data conducted by the researcher on the pharmaceutical logistics officer of RSI Ibnu Sina Padang, it is known that in January-April 2020 there was a number of pending prescriptions reaching 5% of the 13 thousand prescriptions per month, because the drug was empty. Several factors cause empty medicines in pharmaceutical warehouses, one of which is due to delayed payments or locks. The purpose of this study is to analyze the factors that cause the occurrence of drug stock out in the pharmacy warehouse of RSI Ibnu Sina Padang. The type of research used in this study is qualitative descriptive research using interview techniques. The results of the research that have been carried out show that there is still a lack of human resources in pharmaceutical warehouses, the budget process for financing has not been carried out on time, and the availability of drugs in pharmaceutical warehouses is not appropriate in terms of quantity. So it is hoped that hospital management can conduct training for warehouse officers regarding drug control systems and training to improve coordination between officers. Make payments on time, do not delay drug payments if they are due or make drug payments before pending drugs so that drug shipments from distributors are not hampered.